2012
DOI: 10.1177/2047487312447845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of left ventricular hypertrophy in patients with hypertension and normal electrocardiogram

Abstract: Background: Electrocardiography (ECG) has low sensitivity for detecting left ventricular hypertrophy (LVH), while echocardiography cannot be routinely performed. Design/methods: In this study we evaluate the prevalence of LVH and diastolic dysfunction in hypertensive patients with normal ECG. We excluded patients with cardiovascular (CV) diseases, diabetes, chronic kidney disease, or presenting ECG-LVH or other ECG anomalies. The enrolled 440 hypertensive patients underwent echocardiographic examination (Acuso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Duration of hypertension was found to be an independent predictor of left ventricular hypertrophy in our study which is consistent with most studies from around the world [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Duration of hypertension was found to be an independent predictor of left ventricular hypertrophy in our study which is consistent with most studies from around the world [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Until now, only a small number of prediction models for left ventricular mass have been reported. 6 , 7 , 8 , 9 However, most of these models were designed using the Caucasian populations. Previous studies have proposed that ethnic disparities in the prevalence of LVH exist.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that concentric LV remodeling was the most common geometric pattern (9.4%), followed by eccentric non-dilated LVH (6.3%). Compared to normal LV geometry, concentric LVH predicted cardiovascular risk of cardiovascular mortality by 4.04fold, dilated LVH by 3.83-fold, and eccentric nondilated LVH by 2.61-fold after adjustment for baseline covariates, including ambulatory blood pressure [13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 97%